Do Laparoscopic Colorectal Procedures Need Fluid Optimization? - Jenko, Matej; Markovič-Božič, Jasmina; Spindler-Vesel, Alenka (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Goal-directed fluid therapy (GDFT) with hemodynamic monitoring may not be of benefit to all elective patients undergoing major abdominal surgery, particularly those managed in enhanced recovery after surgery protocols (ERAS) setting. AIMS: We predicted different fluid and vasoactive drug consumption during the procedure and less complications in the group of patients, where invasive hemodynamic monitoring was used. METHODS: Two groups of patients undergoing elective laparoscopic colorectal surgery were compared: A control group (CG), with standard hemodynamic monitoring, and a study group, (SG) with invasive hemodynamic monitoring and appropriate intraoperative interventions. We compared differences in intraoperative fluid consumption, length of hospital stay (LOS) and post-operative morbidity. RESULTS: A group of 29 patients in SG had similar average intraoperative fluid balance (+438 mL) as 27 patients in CG (+345 mL) p = 0.432. Average LOS was 8 days (±4) in SG and 6 days (±1) in CG (p = 0.124). Acute renal failure, anastomotic dehiscence, and indication for antibiotic treatment were predictors of statistically significant prolongation of hospital stay 3rd day after surgery, but independent of SG. CONCLUSION: Since no differences between the groups were shown in overall fluid and vasoactive drug consumption, we conclude that GDFT is not needed in laparoscopic colorectal surgery, when ERAS is followed.